Homeostasis of primary and secondary metabolites - Olivares, Philip (2019)
The ability for an organism to maintain homeostasis is of the utmost importance from the smallest single-celled lifeform, to the largest blue whale. While the needs of these organisms may vary widely based on their environments, analogous processes are at play. In this thesis, I will describe my doctoral work towards structurally and functionally understanding how a few of these systems, from single celled prokaryotes like streptomycetes and pseudomonads to an Antarctic fish, allow these organisms to survive and thrive in their respectively harsh environments. Starting on the smallest size scale and the uptake of nutrients for use in central metabolism by a single-celled organism from its environment, I investigate a solute binding protein called HtxB from Pseudomonas stutzeri WM88. This protein has been show to be involved in the uptake of reduced phosphorus compounds such as phosphite and hypophosphite when the more widely available phosphate is not available for utilization as a phosphorus source. Phosphorus, being needed for the synthesis of many biomolecules such as phospholipids, DNA, RNA, and ATP, can easily be the mass limiting element halting further cell division. In this research, I show high resolution crystal structures of HtxB bound to hypophosphite (1.95 Å), phosphite (1.03 Å), and methylphosphonate (1.14 Å), while also interrogating their binding through microscale thermophoresis and surface plasmon resonance. Moving on to the larger scale of intra-bacterial communication through signaling molecules, I investigate the crystal structures of ScbR2, a pseudo-gamma butyrolactone receptor, and AvaR1, the first known butenolide receptor. Both of these receptors are members of a larger class of homologous proteins found throughout streptomycetes involved in the regulation of secondary metabolism. Of these homologous transcriptional repressors, three main classes are known, while all respond to membrane diffusible secondary metabolites. The largest and most well studied class are the gamma-butyrolactone ...